2005
DOI: 10.2527/2005.8351088x
|View full text |Cite
|
Sign up to set email alerts
|

Splanchnic metabolism of nutrients and hormones in steers fed alfalfa under conditions of increased absorption of ammonia and L-arginine supply across the portal-drained viscera1,2,3

Abstract: Effects of increased ammonia and/or arginine absorption on net splanchnic (portal-drained viscera [PDV] plus liver) metabolism of nonnitrogenous nutrients and hormones in cattle were examined. Six Hereford x Angus steers (501 +/- 1 kg BW) prepared with vascular catheters for measurements of net flux across the splanchnic bed were fed a 75% alfalfa:25% (as-fed basis) corn and soybean meal diet (0.523 MJ of ME/[kg BW(0.75).d]) every 2 h without (27.0 g of N/kg of DM) and with 20 g of urea/kg of DM (35.7 g of N/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Regulation of urea transport across the rumen wall (Rojen et al, 2011), for example, decouples the extent of N recycling from N intake making the number of biochemical transformations that a N-containing molecule undergoes before excretion impossible to estimate at this time. Maltby et al (2005) found that ureagenesis accounted for <5% of liver O 2 consumption when they measured hepatic O 2 consumption in steers fed high-protein diets. Thus, the additional energy required for metabolizing and excreting N beyond the energy required for ureagenesis is likely the result of several different biochemical and metabolic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of urea transport across the rumen wall (Rojen et al, 2011), for example, decouples the extent of N recycling from N intake making the number of biochemical transformations that a N-containing molecule undergoes before excretion impossible to estimate at this time. Maltby et al (2005) found that ureagenesis accounted for <5% of liver O 2 consumption when they measured hepatic O 2 consumption in steers fed high-protein diets. Thus, the additional energy required for metabolizing and excreting N beyond the energy required for ureagenesis is likely the result of several different biochemical and metabolic processes.…”
Section: Discussionmentioning
confidence: 99%
“…As a precursor of polyamines and nitric oxide (NO), ARG could improve nitrogen metabolism, angiogenesis and lactogensis (Morris, 2006;Kim and Wu, 2009). L-arginine supplementation increases milk production in cattle and growth hormone in sheep (Chew et al,1984;Davenport et al, 1990aDavenport et al, , 1990b, plasma flow in the portal and hepatic veins in steers (Maltby et al, 2005), and stimulates the production of luteinizing hormone in prepubertal ewes (Recabarren et al, 1996). Recently, injected Arg-HCl has decreased embryonic loss in ewes (Luther et al, 2008), increased lamb birth weight in gestationally nutrient restricted ewes (Lassala et al, 2010), and improved fetal lamb survival to term in prolific ewes (Lassala et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, ‐stimulated ureagenesis could reduce the energy available for productive purposes. In experiments in vivo where portal flow was increased continuously, liver O 2 consumption linked to metabolism varied, however, from no change (Maltby et al., 2005a,b) to 1.2 mol O 2 /mol converted to urea (Milano et al., 2000), with the interpretation of the data complicated either because of the relatively small increase in liver uptake (Maltby et al., 2005a,b) or the confounding effects of higher amino acid absorption across the PDV (Milano et al., 2000). In addition, appears to interfere with liver glucose metabolism.…”
Section: Introductionmentioning
confidence: 99%